An improved culturing method for opiine fruit fly parasitoids and its application to parasitoid monitoring in the field. (24th November 2016) - Masry, Ayad; Furlong, Michael J.; Clarke, Anthony R.; Cunningham, John Paul
Abstract: Good culturing methods play an important role in the study of insect behavior and its application to pest management. Here, we describe and validate a new method for rearing the parasitoid wasp, Diachasmimorpha kraussii, which attacks some of the world's worst fruit fly pests and is an internationally used biological control agent. Our method differs from standard culturing approaches by presenting adult wasps with host‐infested artificial media within a "culturing bag, " which mimics a natural (fruit) oviposition substrate. In laboratory trials using wild collected D. kraussii, the culturing bag method was compared to the use of host‐infested nectarines, and a commonly used laboratory method of presenting host‐infested artificial media within Petri dishes. The culturing bag method proved to be a significant improvement on both methods, combining the advantages of high host survival in artificial media with parasitism levels that were the equivalent to those recorded using host‐infested fruits. In our field study, culturing bags infested with the Queensland fruit fly, Bactrocera tryoni, and hung in a mixed peach and nectarine orchard proved to be effective "artificial fruits" attracting wild D. kraussii for oviposition. Significantly more adult wasps were reared from the culturing bags compared to field collected fruits. This was shown to be due to higher fruit fly larval density in the bags, as similar percentage parasitism rates were found between the culturing bags and ripe fruits. We discuss how this cheap, time‐efficient method could be applied to collecting and monitoring wild D. kraussii populations in orchards, and assist in maintaining genetic variability in parasitoid laboratory cultures.